Association between marital status and insomnia-related symptoms: findings from a population-based survey in Japan. (6th July 2019) - Kawata, Yumi; Maeda, Mitsuya; Sato, Tomoyo; Maruyama, Koutatsu; Wada, Hiroo; Ikeda, Ai; Tanigawa, Takeshi
Abstract: Background: Marital status is one of the socio-economic factors associated with health. Several studies have indicated a significant association between marital status and insomnia. The increases in the percentages of unmarried people in Japan are expected to produce a significant impact on insomnia. The purpose of this study was to examine the association between marital status and insomnia. Methods: The participants were 35 288 people aged 30–59 years selected from the 2010 comprehensive survey of living conditions. We categorized marital status into five groups: single, married couples living with other family members, married couples living without other family members, widowed and divorced. Insomnia-related symptoms (IRS) were based on the participants who chose the answer, 'I couldn't sleep'. Sex-specific multivariable odds ratios (ORs) and 95% confidence intervals (CI) of IRS according to marital status were calculated using the logistic regression model, which was adjusted for potential confounding factors. Results: The proportions of people with IRS were 2.5% in men and 2.8% in women. The multivariable ORs (95% CI) were 1.15 (0.89–1.49) for single, 1.69 (1.11–2.58) for divorced and 1.01 (0.73–1.39) for married couples living without other family members in men, and 1.56 (1.20–2.03) for single, 2.43 (1.83–3.22) for divorced and 1.31 (1.01–1.71) for married couples living without other family members in women. Conclusions: We found divorced men and single, divorced and married women living without other family members had higher IRS than those who were married couples living with other family members in Japanese. This association was more evident in unemployed men.